Descripción de las técnicas de laboratorio para la identificación de agentes que causan varroa ( Varroa Destructor), Acarapiosis (Acarapis Woodi) y nosemosis (Nosema Apis) - Muñoz Clavijo, Tatiana Isabel; Cumbal Orbes, Emily Dayana (Universidad Antonio Nariño, 2022)
The pathogenic agents of Apis mellifera bees have caused great economic losses that fall both economically and environmentally, but above all to beekeepers. Today the Apis mellifera bees are in great danger due to various agents that cause them to be exterminated but above all the changes that humanity has generated such as the continuous extension of urban areas, deforestation and environmental pollution, in addition to this the Most beekeepers are not aware of the diseases that bees can present, and we will see them include from a simple virus to more complex diseases, causing serious problems in the population and very important economic losses. The purpose of this monograph is to generate impact by transferring knowledge and tools for the better identification of these pathogens in bees and thus be able to introduce better sanitary practices to beekeepers with the information provided, since there is no knowledge of other similar texts.